Proyecto de inversión para la implementación del servicio de broker para la exportación de productos agrícolas no tradicionales del litoral ecuatoriano - Gómez Gutiérrez, Félix Lorenzo (2011)
This project performs an analysis to determine the possibility of making an investment in the implementation of the Broker service for the export of traditional agricultural products of the Ecuadorian coast, from a brief market research on this topic, which was evidenced dissatisfaction of small and medium producers of mango, avocado and passion fruit primarily when selling their products. By implementing a broker we want to exploit the existing market niche and change the wrong idea about doing business with small and medium producers and buyers of fruits. Elaborate the value chain through statistical data, research and surveys, which will help us determine the factors and variables involved in the implementation of such activity, and in this way make way for the structuring of the same in the development of cash flow. Subsequently, by using financial tools, the IRR and Payback, it gives way to estimate the viability and feasibility of the investment and profitability to be achieved with the implementation of the Broker. This topic is presented in three parts. In the first detailed introduction, the second is done an internal analysis of the project; the third part evaluates the project with a financial study and the conclusions.